Comparisons Between Jupiter's X‐ray, UV and Radio Emissions and In‐Situ Solar Wind Measurements During 2007. Issue 6 (3rd June 2020) - Dunn, W. R.; Gray, R.; Wibisono, A. D.; Lamy, L.; Louis, C.; Badman, S. V.; Branduardi‐Raymont, G.; Elsner, R.; Gladstone, G. R.; Ebert, R.; Ford, P.; Foster, A.; et al.
Abstract: We compare Chandra and XMM‐Newton X‐ray observations of Jupiter during 2007 with a rich multi‐instrument data set including upstream in situ solar wind measurements from the New Horizons spacecraft, radio emissions from the Nançay Decametric Array and Wind/Waves, and ultraviolet (UV) observations from the Hubble Space Telescope. New Horizons data revealed two corotating interaction regions (CIRs) impacted Jupiter during these observations. Non‐Io decametric bursts and UV emissions brightened together and varied in phase with the CIRs. We characterize three types of X‐ray aurorae: hard X‐ray bremsstrahlung main emission, pulsed/flared soft X‐ray emissions, and a newly identified dim flickering (varying on short time scales, but quasi‐continuously present) aurora. For most observations, the X‐ray aurorae were dominated by pulsed/flaring emissions, with ion spectral lines that were best fit by iogenic plasma. However, the brightest X‐ray aurora was coincident with a magnetosphere expansion. For this observation, the aurorae were produced by both flickering emission and erratic pulses/flares. Auroral spectral models for this observation required the addition of solar wind ions to attain good fits, suggesting solar wind entry into the outer magnetosphere or directly into the pole for this particularly bright observation. X‐ray bremsstrahlung from high energy electrons was only bright for one observation, which was during a forward shock. This bremsstrahlung was spatially coincident with bright UV main emission (power > 1 TW) and X‐ray ion spectral line dusk emission, suggesting closening of upward and downward current systems during the shock. Otherwise, the bremsstrahlung was dim, and UV main emission power was also lower (<700 GW), suggesting their power scaled together. Key Points: We characterize three types of X‐ray aurorae (main oval, ir/regular pulses, and flickering aurorae) and compare with radio, UV, and solar wind data Non‐Io decametric bursts occurred with UV auroral brightening, and UV and hard X‐ray main auroral emission also brightened contemporaneously Soft X‐ray aurora was best fit by iogenic (S, O) spectral lines except during magnetospheric expansion when solar wind ion lines were needed